SYNTHESES OF 2-ISOPROPYL-5-METHYLPHENYL 2-((DIETHYLCARBAMOTHIOYL) THIO) ACETATE (Scientific journal of the Fergana State University, 2024)
The article presents the reaction of O-chloroacetylthymol with sodium diethyldithiocarbamate. 2-Isopropyl-5-methylphenyl 2-((diethylcarbamothioyl) thio) acetate was obtained in high yield under the conditions of interphase catalysis. The structures of the obtained compounds were studied by 1H- and 13C- NMR spectroscopy methods.